2019
DOI: 10.1007/s00284-019-01727-3
|View full text |Cite
|
Sign up to set email alerts
|

First Insight into the Technological Features of Lactic Acid Bacteria Isolated from Algerian Fermented Wheat Lemzeiet

Abstract: Fermented cereals are part of the main traditional diets of many people in Africa, usually obtained from artisanal production. The intensification of their manufacturing, responding to the consumers demand, requires a better control to ensure their sanitary, nutritional, and taste qualities, hence, the need of selecting accurate and safe starter cultures. In the present study, 48 lactic acid bacteria (LAB) strains, previously isolated from Algerian fermented wheat lemzeiet, were analyzed for different technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…The selected pure strains of the new LAB were assessed for their ability to produce organic acids in sterile broths extracted from the flours of the pseudocereals quinoa and buckwheat and the vegetable chickpea, following the procedures described previously [74] with slight modifications. Chickpea, quinoa, and buckwheat were ground in a coffee mill (Bosch, Cluj, Romania) before sampling.…”
Section: Evaluation Of the Acidification Capacity Of Presumptive Lactmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected pure strains of the new LAB were assessed for their ability to produce organic acids in sterile broths extracted from the flours of the pseudocereals quinoa and buckwheat and the vegetable chickpea, following the procedures described previously [74] with slight modifications. Chickpea, quinoa, and buckwheat were ground in a coffee mill (Bosch, Cluj, Romania) before sampling.…”
Section: Evaluation Of the Acidification Capacity Of Presumptive Lactmentioning
confidence: 99%
“…growth and, therefore, to avoid the production of their mycotoxins. Other lactic acid bacteria strains with antimicrobial effects against several pathogens were found, for instance, in some spontaneous wheat, rye, and sorghum sourdoughs [74,[85][86][87][88] or home-made cheeses [89,90]. Furthermore, a study regarding a Chinese sourdough revealed that most of the isolated strains belonged to the Lactobacillus spp., followed by Pediococcus spp.…”
Section: Selection Of Presumptive Lactic Acid Bacteria Strains Based mentioning
confidence: 99%
“…While the production of extracellular lipases was tested by the presence of a clear halo around and under the strain's spots at the surface of MRS agar containing (1% v/v) Tween 80 and Tween 20 after incubation at 35C for 24 h to 72 h (Merabti et al, 2019). Each test was performed in triplicate.…”
Section: Proteolytic and Lipolytic Activitymentioning
confidence: 99%
“…These technological features are promising for future application in fermented products such as yogurt and acidified milk. The literature shows that some strains of Lactiplantibacillus pentosus isolated from raw cereal material had a high acidification power (Merabti et al, 2019). However, L. brevis 91 and L. brevis 110 were not able to acidify milk during the 24 h fermentation time (pH 5.35 and 5.07, respectively); according to González et al (2010), these findings may be due to the slow rate at which the lactose is metabolized by the Lactobacillus genus.…”
Section: Acidification Capacity and Viability During Stockage Periodmentioning
confidence: 99%
“…Corsetti et al (2007) reported that E. casselivaflavus, E. durans, E. feacalis, E. faecium and E. mundtti were the most prevalent enterococci species in Italian wheat grain and nonconventional flour. Studies on the microbiota of Algerian fermented wheat Lemzeiet or El-Hammoum revealed that three isolates were identified as E. faecium (Merabti et al, 2019).…”
Section: Fig4mentioning
confidence: 99%